Dry eye in Parkinson's disease: a narrative review - Ungureanu, Larisa; Chaudhuri, K. Ray; Diaconu, Stefania; Falup-Pecurariu, Cristian (Frontiers in Neurology, 2023)
In Parkinson's disease (PD) patients a wide range of ocular and visual disorders are present. Tear film instability, inflammation and dysfunction of the ocular surface and the presence of symptoms of visual disturbance characterize dry eye, a multifactorial disease of the ocular surface. Based on a literature search we discuss the frequency, pathogenesis and influence on quality of life of dry eye in Parkinson's disease. Furthermore, we review the available means of diagnosis and management of dry eye. An improvement of awareness and recognition of dry eye is needed in order to provide suitable, personalized therapeutic options for PD patients, aiming to improve their quality of life, independence and safety.